A estética vernacular como retórica visual da publicidade gráfica - Dones, Vera Lúcia (2013)
This thesis aims at understanding the role of the vernacular aesthetics as a rhetorical element in advertising messages. We have proposed a reflection on what we has been called 'vernacular', which is characterized as an aesthetical dimension of contemporary culture. In Chapter I, we have both gathered information that contribute to the presentation of the concept of 'vernacular', and presented the contexts and conditions that have given way to its production in graphical communication, based on what has been noticed in graphical pieces, brands, typography, advertisements and visual arts. In Chapter II, we have problematized rhetoric in the field of visual communication in order to find out the persuasive aspects of visual language in advertising. In Chapter III, we have analyzed three advertisements with the aim of determining the type of communicative function of the vernacular in advertising messages, and rhetorical-visual arguments between the different message agents. The appropriations of the vernacular in visual communication have been inserted into the culture of reproduction and copy, and they are related both to the simulacrum that characterizes our time, and to the indexation of forms that have been despised or that are allegedly naïve. We have concluded that the vernacular aesthetics, as visual rhetoric of graphical advertising, is a metaphor of authenticity . This occurs when images, letterings, writings constructed with improbable materials, and native graphical expressions, among others, end up fostering a kind of economy of arguments, since the symbolisms presented by the referents say more and convince better than the conventional iconograms used in advertising communication.